Consideraciones de Merleau-Pontyan en la educación matemática: los focos de investigación evidenciados entre 2013 y 2017 - de Andrade Viana, Elton (2022)
Considering a discussion, under the prism of the Phenomenology of Perception developed by Maurice Merleau-Ponty (1908-1961), it is possible to observe that Mathematics Education has shown interest in the postulates of this philosopher through the research being carried out in the Brazilian territory. In order to identify the research approach, based on Merleau-Ponty's postulates and in the area of Mathematics Education, we elaborated a study that allows us to visualize the research scenario of the last five years regarding the use of this philosopher as a theoretical reference. The research has a qualitative approach and the data production is carried out through a documentary analysis. The results showed the existence of three research axes: the student, the teacher and teaching, being the teacher the research axis with more evidence in the works considered so far.